A contextualized IT adoption and use model for telemedicine in Ethiopia. Issue 2 (3rd April 2019) - Mengesha, Getachew Hailemariam; Garfield, Monica J.
ABSTRACT: Health care is a critical contributor to the socioeconomic development of a country. Telemedicine systems can improve health care within such countries. This study develops a telemedicine adoption and use model that embraces psychosocial, behavioral, work process, and organizational-related variables that impact a physician's adoption and continuance of use of telemedicine. Two hundred and five questionnaires from medical professions at the Black Lion Hospital, Addis Ababa, Ethiopia, were used in this study. The study found that "Facilitating conditions, " "Compatibility with medical practice" and "Compatibility with physicians preferred work style" are the most prominent constructs in the study context. These findings suggest that the external environment in which a telemedicine system is used will have a significant impact on its use. Therefore, when a telemedicine system is transferred from a developed country to a less-developed country, we will likely see different issues arise in the adoption and use of the system.